Web appendices - Exploring the antecedents of customers’ willingness to use service robots in restaurants. - Molinillo-Jiménez, Sebastián; Rejón-Guardia, Francisco; Anaya-Sánchez, Rafael (My University, 2022)
In recent times researchers have begun to use several theories to explain how relationships develop between service robots and consumers, and to identify the reasons and motives consumers use these technologies. In this sense, Web Appendix A shows a non-exhaustive list of recent relevant articles on service robot adoption in the hotel and restaurant industries (sorted from highest to lowest citations). Besides, in this research the respondents, prior to answering the questionnaire, randomly viewed one of two videos showing similar service robots operating in two restaurants (Web Appendix B).
Keywords: Robots autónomos; Hostelería; Restaurantes, cafeterías, etc.; Service robots; Willingness to accept